Hybrid hydrogels containing gradients in gold nanoparticles for localized delivery of mesenchymal stem cells and enhanced nerve tissues remodeling in vivo - Jie Gao; Yiduo Zhou; Gang Xu; Zhongqing Wei; Liucheng Ding; Wei Zhang; Yi Huang (Materials Today Bio)
Currently, most peripheral nerve injuries are incurable mainly due to excessive reactive oxygen species (ROS) generation in inflammatory tissues, which can further exacerbate localized tissue injury and cause chronic diseases. Although promising for promoting nerve regeneration, stem cell therapy still suffers from abundant intrinsic limitations, mainly including excessive ROS in lesions and inefficient production of growth factors (GFs). Biomaterials that scavenge endogenous ROS and promote GFs secretion might overcome such limitations and thus are being increasingly investigated. Herein, firstly reported as specific ROS scavenging agents and paracrine stimulators, gold nanoparticles (GNPs) were incorporated in the chitosan/polyvinyl alcohol hydrogel networks. The GNPs/hydrogel composite can support the survival of mesenchymal stem cells (MSCs) with excellent expansion efficiency and protect MSCs in a simulated ROS microenvironment, decreasing the intracellular ROS levels and simultaneously enhancing cell viability. Moreover, biodegradable scaffolds, along with MSCs, were implanted into sciatic nerve defects in a rat model to show good application value in vivo. Our work demonstrated that the GNPs/hydrogel shows great promise in MSCs therapy for peripheral nerve injury with convincing biological evidence.